Abu Ubaid sebagai Fuqha’ dan Ekonom: Critical Reading terhadap Corak Pemikiran dan Konsepsi Ekonomi Ibn Ubaid - Hidayat, Taufik (AL-FALAH : Journal of Islamic Economics, 2019)
Purpose: The purpose of this article is to critically examine the style of thought and economic conception offered by Ibn Ubaid, in his Al-Amwal work. This critical reading is intended so that the scientific structure of Islamic economics presented in the book of Al-Amwal, can be identified more firmly and clearly.Design/Methodology/Approach: This paper explores critically the economic conception of Ibn Ubaid, and then formulates how the style of thinking Ibn Ubaid. With a qualitative approach, with the design ofresearch hermeneutics, this paper is expected to be able to interpret Ibn Ubaid's thinking more systematically.Findings: This study offers two theses: First, from the work and structure of the arguments found consistently in the book of Al-Amwal, Ibn Ubaid is actually the figure of a prolific jurist. He consistently uses fiqh reasoning in elaborating an economic issues. Second, the economic concepts offered by Ibn Ubaid are fragmented, or fragmented. He is more concerned with discussing public finance. He offers the concept of a tax system based on social justice, or tax collection must be based on a fair system. So that taxes are not an instrument of exploitation of the people.Originality/Value: The contribution of this paper lies in the answer to the emptiness of the literature that critically examines the book of Al-Amwal, and is able to identify the dominant patterns of thought of Ibn Ubaid.